Detection of new mutations in six out of 10 Swiss HNPCC families by genomic sequencing of the hMSH2 and hMLH1 genes. Issue 11 (November 1995) - Buerstedde, J M; Alday, P; Torhorst, J; Weber, W; Müller, H; Scott, R
Abstract : The cancer predisposition in most HNPCC families is believed to be associated with mutations in the human mismatch repair gene homologues hMSH2 and hMLH1. We searched for mutations in our collection of 10 Swiss HNPCC families by sequencing the exons and exon/intron boundaries of the hMSH2 and hMLH1 genes. In four families we found different mutations which are expected to lead to protein truncations of either the hMSH2 or the hMLH1 proteins owing to premature in frame stop codons or splice defects. In two more families we detected mutations leading to an amino acid deletion and an amino acid substitution in an evolutionary conserved residues respectively. None of these mutations has been reported in other families, which is consistent with the notion that HNPCC associated hMSH2 and hMLH1 mutations are heterogeneous and there is no striking founder effect in the Swiss population. Whenever this could be investigated, the presence of the mutations was confirmed in other family members who showed manifestations of HNPCC. Interestingly, an obligate carrier in one of the families developed a brain tumour at the age of 29, histologically verified as a glioblastoma multiforme, which was recently linked to HNPCC in the context of Turcot's syndrome.